ESENSI KEHIDUPAN MANUSIA DALAM TEKS GEGURITAN AJI SESANA - Widiantana, I Kadek (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2019)
Lack of knowledge of the nature of life, especially being human, impacts many experiencing stress symptoms, even at the rise of suicides cases. Therefore, it is important to understand the essence of being born human, so that you can live your life as well as possible. One of the Geguritan texts that contains the essence of life being human is the Geguritan Aji Sesana which is considered to be lacking in attention. Therefore, the author uses this Geguritan as a study material, because in the Geguritan summarized the teachings of Hinduism, mainly related to the essence of being born into a human, so that there is no regret to be human. Based on the explanation above, in this paper will discuss about:1) Structure of the Geguritan Aji Sesana; and 2) The essence of human life in the Geguritan Aji Sesana. In analyzing the Geguritan Aji Sesana text, the author uses structural and semiotic theories.The Geguritan Aji Sesana is a text that contains the essence of being born human, how humans must always cling to the teachings of Dharma, with the essence of being born the main human being. Humans are reminded to always be vigilant with enemies that are in themselves because the enemy is actually inside. Humans are required to always improve themselves by diligently studying literature. But in studying the literature, it must be gradual and begin from the basic level.